Life and work of Margaret Gatty (1809–1873), with particular reference to British sea-weeds (1863). Issue 1 (April 2016) - Bryant, J. A.; Plaisier, H.; Irvine, L. M.; McLean, A.; Jones, M.; Spencer Jones, M. E.
Abstract : Mrs Margaret Gatty took up beachcombing, especially collecting and identifying seaweeds, in middle age and improved her expertise through correspondence with some of the most prominent scientists of the day. In particular, she formed an important relationship with William Henry Harvey, which was of benefit to them both. Mrs Gatty's major publication, British sea-weeds, demonstrates her powers of observation and interpretation. A new study of her correspondence has clarified a link between British sea-weeds and two works by Harvey, Phycologia britannica and The atlas of British seaweeds, as well as the status of an unpublished work Mrs Gatty called her "Horn-book of phycology".